Base isolation for retrofitting historic buildings evaluation of seismic performance through experimental investigation. - De Luca, Antonello (Earthquake engineering & structural dynamics.)
An experimental test program on a full scale model representing a sub-assemblage of the cloister facade of the Sao Vicente de Fora monastery, retrofitted through base isolation, has been recently carried out at the European Laboratory for Structural Assessment of the Joint Research Centre of the European Commission. In this paper an overview of the laboratory model and the experimental results is provided. In particular, firstly the test model is described, including the geometry and mechanical properties of the masonry specimen and the design of the isolation devices; then the testing method and the substructuring of the isolation system are described and the seismic inputs adopted for the pseudo dynamic tests are defined. Finally, the experimental results are discussed and compared to the analogous results obtained on the 'as is', fixed base sub assemblage model. The implications of the test outcomes are emphasized and developments of this research line are presented.